2012
DOI: 10.1371/journal.pntd.0001804
|View full text |Cite
|
Sign up to set email alerts
|

Differential Infectivity by the Oral Route of Trypanosoma cruzi Lineages Derived from Y Strain

Abstract: BackgroundDiversity of T. cruzi strains is a central problem in Chagas disease research because of its correlation with the wide range of clinical manifestations and the biogeographical parasite distribution. The role played by parasite microdiversity in Chagas disease epidemiology is still debatable. Also awaits clarification whether such diversity is associated with the outcome of oral T. cruzi infection, responsible for frequent outbreaks of acute Chagas disease.Methods and FindingsWe addressed the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
1
15
0
1
Order By: Relevance
“…Using immunofluorescence microscopy with a monoclonal antibody to the ubiquitous lysosomal protein Lamp-2, we ascertained that lysosomes were mobilized to the cell periphery upon interaction with SAP-CE, but not with GST (Figure 5D). Lysosome distribution, similar to that induced by recombinant SAP-CE has been observed upon incubation of HeLa cells with recombinant proteins based on molecules implicated in promoting metacyclic trypomastigote internalization, such as GP30 and GP82 [47], [48]. Addition of SAP-CE protein did not result in marked pH change that could influence the lysosome mobilization.…”
Section: Resultssupporting
confidence: 65%
“…Using immunofluorescence microscopy with a monoclonal antibody to the ubiquitous lysosomal protein Lamp-2, we ascertained that lysosomes were mobilized to the cell periphery upon interaction with SAP-CE, but not with GST (Figure 5D). Lysosome distribution, similar to that induced by recombinant SAP-CE has been observed upon incubation of HeLa cells with recombinant proteins based on molecules implicated in promoting metacyclic trypomastigote internalization, such as GP30 and GP82 [47], [48]. Addition of SAP-CE protein did not result in marked pH change that could influence the lysosome mobilization.…”
Section: Resultssupporting
confidence: 65%
“…Experiments with metacyclic forms of T. cruzi strain Y82, which also engage gp82 to invade host cells (45), revealed that FN inhibits parasite entry into host cells when present at concentrations higher than the cruzipain activity can fully digest, and that treatment of target cells with the recombinant cruzipain increases parasite internalization, whereas the cysteine proteinase inhibitor has the opposite effect (data not shown). Unlike CL and Y82 strains, G strain metacyclic forms, which are less invasive toward human epithelial cells, lacked cruzipain activity.…”
Section: Discussionmentioning
confidence: 97%
“…cruzi strains that do not express gp82 on the surface have reduced gastric mucin-binding capacity and, as compared to gp82-expressing MT, they migrate less effi ciently through the gastric mucin-coated transwell fi lter and are poorly infective in mice by the oral route (Cortez et al 2003(Cortez et al , 2012b. Gp82 is engaged by MT of highly infective T .…”
Section: Gastric Mucin-binding Property Of Gp82 and Mt Migrationmentioning
confidence: 99%